Efforts to Increase Student Activity and Learning Outcomes on Identifying Types of Pests and Vegetable Through Experimental Methods - Nani Nur’aeni (Ridwan Institute, 2022)
This research is motivated by the low activity and learning outcomes of vegetable agribusiness to identify the types of pests and diseases of vegetable crops. This research is focused on the application of the experimental method. This type of research is Classroom Action Research (CAR) which adapts the Kemmis & Mc. Taggart with two cycles, which in each cycle two actions are performed. The subjects of this study were students of class XI ATPH 3 SMK Negeri 1 Losarang, totaling 36 students. Methods of data collection with the technique of observation, tests and documentation. Validation of data using triangulation technique. The data analysis used is a comparative descriptive analysis technique. The results of data analysis showed that the application of the experimental method was proven to be able to increase student activity and learning outcomes. An increase in learning activity from the initial conditions of 14 students or 38.89%, increased to 22 students or 61.11% in the first cycle, and 94.44% or 34 students in the second cycle, and an increase in student learning outcomes from the average in the second cycle. before the improvement was only 62.22, increased to 75.00 in the first cycle, and 85.86 in the second cycle, with a learning mastery level of 11 students (30.56%) in the initial conditions, 58.33% or 21 students in the first cycle. first, 31 students or 86.11% in the second cycle, and there are still 5 students (13.89%) who have not completed, so that all the criteria for completeness have been achieved in the second cycle. The conclusion is that the experimental method approach is proven to increase the activity and learning outcomes of students in class XI ATPH 3 SMK Negeri 1 Losarang Semester 1 of the 2020/2021 academic year in learning vegetable crop agribusiness on the subject of identifying the types of pests and diseases of vegetable crops.